Casual Employment and Its Consequences: A Historical Appraisal of Recent Labour Market Trends. Issue 40 (September 2019) - Whiteside, Noel
Abstract : The spread of what are called 'irregular' or 'non-standard' jobs, rising female economic activity rates and the appearance of new 'gig', 'sharing', or 'crowd' work have promoted changed forms of employment to create a 'modern' labour market. This paper revisits employment during the late nineteenth century, revealing how, in major commercial centres, workers adopted idiosyncratic ways of earning a living in order to make ends meet. This invites two observations. First, the present-day labour market is less 'modern' than is supposed. Second, the 1940s to 1960s emerged as the era when 'traditional', permanent employment covered the bulk of the working population, with complementary social insurance to protect against risk. The post-1945 settlement was a political product, underwritten by the state, whose roots can be traced back to pre-1914 policy debates on labour market reform. If, as appears the case, this settlement has had its day, what risks do we run as we revert to employment practices characteristic of a much earlier age?